PENGARUH SHOPPING LIFESTYLE, FASHION INVOLVEMENT DAN HEDONIC SHOPPING VALUE TERHADAP IMPULSE BUYING BEHAVIOUR PELANGGAN TOKO ELIZABETH SURABAYA - PRASTIA, FITA EKA (Universitas Katolik Widya Mandala Surabaya, 2013)
Along with the variated needs of consumers who provide business opportunities for businesses, especially in the field of fashion. This fact led many pop stores that sell a variety of types of fashion products for both men and women. This phenomenon is well responded by the Elizabeth Store is one of the famous stores with a great selection of quality fashion products with prices. This study aims to determine the influence of shopping lifestyle, fashion involvement, and hedonic shopping value towards impulse buying behavior customers Elizabeth Surabaya Store. This study is a causal hypothesis and using purposive sampling in sampling. Characteristics of the respondents surveyed were respondents who are aged> 18 years and never shopped at Elizabeth Surabaya Store at least 2 times in the last five months the number of those 100 people. The analysis technique used is the multiple regressions linear. Results of this study showed that variables shopping lifestyle, Fashion involvement, and Hedonic Shopping Value positive significantly influence Impulse buying behavior.